Effects of Combined Pharmaceutical Care and Pulmonary Rehabilitation Program on Chronic Obstructive Pulmonary Disease Patients - Panthong, Kritsana; Aungkapattamagul, Sariya; Phromin, Wiliwan; Chaokamut, Chulalak (JOURNAL OF LOEI PROVINCIAL PUBLIC HEALTH OFFICE, 2025)
This quasi-experimental research aimed to study the effectiveness of a pharmaceutical care program in conjunction with pulmonary rehabilitation for patients with chronic obstructive pulmonary disease (COPD), compared to standard care. The sample consisted of 26 COPD patients who received services at the outpatient department of Nong Hin Hospital, Loei Province. The sample size was calculated using a formula for comparing the means of two dependent groups, resulting in an experimental group and a control group, each with 13 patients. The experimental group received the pharmaceutical care program along with pulmonary rehabilitation for COPD patients. The research instruments included the pharmaceutical care program with pulmonary rehabilitation, an assessment form for the correct use of MDI and DPI inhalers, a lung function measuring device, and the 6MWT test. Data collection was conducted in two phases: before and after the experiment. Data were analyzed using descriptive statistics, including percentage, mean, standard deviation, and confidence interval, and inferential statistics using the paired t-test. The results showed that COPD patients in the experimental and control groups had mean lung function (PEFR%) values of 58.23 (S.D. = 5.53) and 60.46 (S.D. = 6.15), respectively, with no statistically significant difference (t = 0.27, df = 12, p-value < 0.78) at a 95% confidence level. Although the mean lung function of both groups did not differ, when considering the severity of the disease, it was found that the experimental group experienced improved symptoms after the experiment. The program also resulted in patients having correct medication use techniques, increased medication adherence, and the ability to resolve side effects and problems arising from medication use. Therefore, to maximize the effectiveness of treatment for COPD patients, in addition to medication adherence and correct medication use techniques, exercise to rehabilitate lung function is another method that can further enhance the effectiveness of disease control.